Evaluation of Erythrocyte Indices in Newborn According to Gestational Age (Bangladesh Journal of Child Health, 2018)
Background: The normal hematological values in newborns differ significantly from those of infants, older children and adults. In our observation, the values of the newborn babies vary according to the gestational age. At birth the hemoglobin, hematocrit, mean corpuscular volume and mean corpuscular hemoglobin of term newborns are significantly higher than those of older infants and children, and in preterm newborns the differences are even more pronounced. The objective of this study is to evaluate the erythrocyte indices in preterm and term newborns at birth.Methodology: This cross sectional study was conducted in the department of Neonatology in BSMMU from May 2014 to April 2015. A total of 86 newborns; 48 term and 38 preterm were included in the study. Newborns were divided into two groups- term group and preterm group. Erythrocyte indices: hemoglobin (Hb), hematocrit (Hct), red blood cell (RBC) count, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red cell distribution width (RDW) were estimated from cord blood immediately after birth.Results: Mean hemoglobin level in term group was 15.65±1.04g/dl and preterm group was 15.21±0.93g/dl; this difference was statistically significant (p